Are Trombe walls suitable passive systems for the reduction of the yearly building energy requirements?. (15th October 2019) - Bevilacqua, Piero; Benevento, Federica; Bruno, Roberto; Arcuri, Natale
Abstract: Efficient low consumption buildings require the building envelope to be scrupulously designed from an early stage. Passive solar technologies, such as the Trombe wall, can contribute to the reduction of the heating energy demand and, if properly operated, they can also impact the building summer behaviour. The use of such a solution has been limited, especially in warm climates, as severe problems of indoor overheating can occur even beyond the cooling period. Through the dynamic simulation software DesignBuilder, the authors investigated the energy performance of two different residential buildings equipped with a Trombe wall in different climatic contexts. The authors proposed the adoption of proper ventilation strategies to further reduce cooling needs. The validity and effectiveness of the proposed solutions was verified in warm climates where the Trombe reduced heating requirements by up to 71.7% and decreased the cooling energy demand by 36.1%. In a cold climate, heating savings were 18.2% with a cooling energy reduction of 42.4%. The study highlighted the fundamental importance of the definition of proper ventilation strategies based on climatic parameters to prevent drawbacks in intermediate seasons, with an evident limitation of the system performance. Highlights: Summer and winter dynamic performance of a Trombe wall was assessed in three localities. Summer ventilation strategies of a Trombe wall have been investigated. Considerable reductions of yearly energy requirements were found.